2020
DOI: 10.1021/acs.biochem.0c00224
|View full text |Cite
|
Sign up to set email alerts
|

An Ambidextrous Polyphenol Glycosyltransferase PaGT2 from Phytolacca americana

Abstract: The glycosylation of small hydrophobic compounds is catalyzed by uridine diphosphate glycosyltransferases (UGTs). Because glycosylation is an invaluable tool for improving the stability and water solubility of hydrophobic compounds, UGTs have attracted attention for their application in the food, cosmetics, and pharmaceutical industries. However, the ability of UGTs to accept and glycosylate a wide range of substrates is not clearly understood due to the existence of a large number of UGTs. PaGT2, a UGT from P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Currently, 24 crystal structures of plant UGTs family 1 are available these include AtUGT72B1, 53 AtUGT74F2, 54 and AtUGT89C1 55 from Arabidopsis thaliana , CtUGT78K6 from Clitoria ternatea , 56 FeUGT708C1 from Fagopyrum esculentum , 57 GgCGT from Glycyrrhiza glabra , 58 UGT73P12 from Glycyrrhiza uralensis (; 7c2x), LpCGTa and b from Landoltia punctate , 59 MtUGT71G1, 60 MtUGT85H2, 61 and MtUGT78G1 62 from Medicago truncatula , Os79 from Oryza sativa , 63 PtigS from Persicaria tinctoria , 64,65 PaGT2 66 and 3 67 from Phytolacca americana , SbCGTa and b from Scutellaria baicalensis , 59 mogrol glucosyltransferase SgUGT74AC1 and AC2 from Siraitia grosvenorii , 39,68 SrUGT76G1 from Stevia rebaudiana , 69–71 C -glycosyltransferase from Trollius chinensis , 72 VvGT1 from Vitis vinifera , 32 and ZmCGTa from Zea mays 59 (). The 3-dimensional structures show remarkable conservation in their secondary and tertiary structures.…”
Section: Strategies For Functional Analysis Of Ugtsmentioning
confidence: 99%
“…Currently, 24 crystal structures of plant UGTs family 1 are available these include AtUGT72B1, 53 AtUGT74F2, 54 and AtUGT89C1 55 from Arabidopsis thaliana , CtUGT78K6 from Clitoria ternatea , 56 FeUGT708C1 from Fagopyrum esculentum , 57 GgCGT from Glycyrrhiza glabra , 58 UGT73P12 from Glycyrrhiza uralensis (; 7c2x), LpCGTa and b from Landoltia punctate , 59 MtUGT71G1, 60 MtUGT85H2, 61 and MtUGT78G1 62 from Medicago truncatula , Os79 from Oryza sativa , 63 PtigS from Persicaria tinctoria , 64,65 PaGT2 66 and 3 67 from Phytolacca americana , SbCGTa and b from Scutellaria baicalensis , 59 mogrol glucosyltransferase SgUGT74AC1 and AC2 from Siraitia grosvenorii , 39,68 SrUGT76G1 from Stevia rebaudiana , 69–71 C -glycosyltransferase from Trollius chinensis , 72 VvGT1 from Vitis vinifera , 32 and ZmCGTa from Zea mays 59 (). The 3-dimensional structures show remarkable conservation in their secondary and tertiary structures.…”
Section: Strategies For Functional Analysis Of Ugtsmentioning
confidence: 99%
“…2 , respectively), while InGTase1 ( Ipomoea nil ) [ 41 ] can catalyze phenylpropanoids and alkaloids ( 7 in Fig. 2 ), PaGT2 ( Phytolacca americana ) [ 42 ] can catalyze phenylpropanoids and polyketides ( 9 in Fig. 2 ), and SaGT4A ( Solanum aculeatissimum ) [ 43 ] can catalyze terpenoids and alkaloids ( 10 in Fig.…”
Section: Gt Diversity In Glycosylated Pnp Synthetic Pathwaysmentioning
confidence: 99%
“…Moreover, the mutation of His20 to Ala or Asp has been shown to completely impair the activity of the enzyme (Ozaki et al, 2012). Another UGT from P. americana, PaGT2, has been shown to possess two catalytic histidines: the conserved catalytic histidine His18 and the alternate catalytic residue His81 (Maharjan, Fukuda, Shimomura et al, 2020). The mutation of either of the catalytic histidines in PaGT2 was compensated by another catalytic histidine, which helped to retain the catalytic activity of the enzyme.…”
Section: Sugar-acceptor Binding In Pagt3mentioning
confidence: 99%
“…In UGT78K6 from C. ternatea, Asp367, Asp181 and the mainchain carbonyl O atom of Pro78 stabilize kaempferol, forming hydrogen bonds to the C5, C7 and C4 0 hydroxyl groups of the acceptor molecule, respectively (Hiromoto et al, 2015). Also, in PaGT2 it has been shown that the 3 0 -OH and 4 0 -OH groups of the piceatannol molecule are stabilized by hydrogen bonds to His81 and Glu82, respectively (Maharjan, Fukuda, Shimomura et al, 2020). However, in PaGT3 the acceptor capsaicin is mainly stabilized by hydrophobic interactions and the only possible hydrogen bond is observed to the catalytic His20.…”
Section: Comparison Of Sugar-acceptor Binding In Pagt3 With That In O...mentioning
confidence: 99%
See 1 more Smart Citation